Characterization of left ventricular myocardial sodium-glucose cotransporter 1 expression in patients with end-stage heart failure - Sayour, Alex Ali (Cardiovasc Diabetol, 2020)
BACKGROUND: Whereas selective sodium-glucose cotransporter 2 (SGLT2) inhibitors consistently showed cardiovascular protective effects in large outcome trials independent of the presence of type 2 diabetes mellitus (T2DM), the cardiovascular effects of dual SGLT1/2 inhibitors remain to be elucidated. Despite its clinical relevance, data are scarce regarding left ventricular (LV) SGLT1 expression in distinct heart failure (HF) pathologies. We aimed to characterize LV SGLT1 expression in human patients with end-stage HF, in context of the other two major glucose transporters: GLUT1 and GLUT4. METHODS: Control LV samples (Control, n = 9) were harvested from patients with preserved LV systolic function who went through mitral valve replacement. LV samples from HF patients undergoing heart transplantation (n = 71) were obtained according to the following etiological subgroups: hypertrophic cardiomyopathy (HCM, n = 7); idiopathic dilated cardiomyopathy (DCM, n = 12); ischemic heart disease without T2DM (IHD, n = 14), IHD with T2DM (IHD + T2DM, n = 11); and HF patients with cardiac resynchronization therapy (DCM:CRT, n = 9, IHD:CRT, n = 9 and IHD-T2DM:CRT, n = 9). We measured LV SGLT1, GLUT1 and GLUT4 gene expressions with qRT-PCR. The protein expression of SGLT1, and activating phosphorylation of AMP-activated protein kinase (AMPKα) and extracellular signal-regulated kinase 1/2 (ERK1/2) were quantified by western blotting. Immunohistochemical staining of SGLT1 was performed. RESULTS: Compared with controls, LV SGLT1 mRNA and protein expressions were significantly and comparably upregulated in HF patients with DCM, IHD and IHD + T2DM (all P < 0.05), but not in HCM. LV SGLT1 mRNA and protein expressions positively correlated with LVEDD and negatively correlated with EF (all P < 0.01). Whereas AMPKα phosphorylation was positively associated with SGLT1 protein expression, ERK1/2 phosphorylation showed a negative correlation (both P < 0.01). Immunohistochemical staining revealed that SGLT1 expression was predominantly confined to cardiomyocytes, and not fibrotic tissue. Overall, CRT was associated with reduction of LV SGLT1 expression, especially in patients with DCM. CONCLUSIONS: Myocardial LV SGLT1 is upregulated in patients with HF (except in those with HCM), correlates significantly with parameters of cardiac remodeling (LVEDD) and systolic function (EF), and is downregulated in DCM patients with CRT. The possible role of SGLT1 in LV remodeling needs to be elucidated.